WORLD ENGINEERING EDUCATION FORUM 2014 IN DUBAI - Hans J. Hoyer; Stephanie Cheng (Высшее образование в России)
The paper describes the World Engineering Education Forum 2014 in Dubai (WEEF 2014). A short history of this event is given. The Global Student Forum before WEEF2014 is described. The attention is drawn to opening ceremony and keynotes, highlights on IGIP, GED and IFEES under WEEF 2014 umbrella. Issues of globalization, joint research, attributes of global engineer, collaboration of universities and corporations, diversity and inclusion are discussed.